Cultural anxieties : managing migrant suffering in France - Larchanché, Stéphanie (Medical anthropology (New Brunswick, N.J.), 2020)
"Cultural Anxieties is a compelling ethnography about Centre Minkowska, a transcultural psychiatry clinic in Paris, France. From her unique position as both observer and staff member, Stéphanie Larchanché explores the challenges of providing non-stigmatizing mental healthcare to migrants, and she identifies practical routes for improving caregiving practices"--